EARNINGS PERSISTENCE AFTER ADOPTION INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) ON REAL ESTATE SECTOR AT THE INDONESIA STOCK EXCHANGE - B421111012, Melati Pramudita Lestari melati (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
ABSTRACT This study aims at empirically testing on the adoption of IFRS increase earnings persistence. The sample of this study was taken from both Real Estate companies that have adopted IFRS in 2013 and 2014 and those that have not adopted IFRS in 2010 and 2011yet. The tests were conducted to see the persistence of earnings by looking at the correlation of earnings persistence at variable debt coverage, operating cycle, and company size. Results of tests performed show that the level of debt, the size of the company's operating cycle did not experience a difference after the adoption of IFRS. Thus, this phenomenon needs more attention from the investors in terms of making investment decisions. Theoretically, the implications of this study show that the persistence of earnings before and after the adoption of IFRS is not relevant when tested using variable levels of debt, operating cycle, and the size of the company. Regarding the aspect of decision-making that uses financial information, it is necessary to conduct an assessment using variables other than those tested in this study, because the variables used in this study did not have a significant effect on the persistence of earnings before and after the adoption of IFRS. The weakness of this study is that its sample was restricted only to the Real estate company. This study was conducted only in two years before and after the implementation of IFRS. Variables used to determine the effects of the persistence of profit before and after IFRS have not represented the impact on the persistence of earnings before and after the adoption of IFRS. Keywords: Persistence of earnings, IFRS, the operating cycle, debt coverage, company size.